1999
DOI: 10.1021/jp984225w
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Mechanisms for the Alkoxyacetic Acids Decomposition

Abstract: The decomposition of three alkoxyacetic acids, methoxy, ethoxy, and isopropoxy acetic acids, has been studied by using ab initio calculations at the MP2/6-31G** level. Molecular mechanisms A and B have been characterized, corresponding to stepwise processes with formation of the corresponding alcohol and an α-lactone intermediate, achieved by the nucleophilic attack of either carbonylic or hydroxylic oxygen atoms followed by a ring opening process to yield formaldehyde and carbon monoxide. For ethoxyacetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
4
26
1
Order By: Relevance
“…A critical concept for understanding fragmentation of glycolate is formation of an ␣-lactone intermediate ion following nucleophilic attack of the carboxylic oxygen on the ␣-carbon. A similar concept for the gas phase reactions of neutral glycolic acid has been postulated before based on theoretical studies on the mechanisms of the decomposition of ␣-hydroxycarboxylic and alkoxyacetic acids [11,12]. We believe that our experimental observations provide a support for ␣-lactone as an intermediate in dissociation reactions of negative ions of glycolic acid.…”
Section: Resultssupporting
confidence: 83%
“…A critical concept for understanding fragmentation of glycolate is formation of an ␣-lactone intermediate ion following nucleophilic attack of the carboxylic oxygen on the ␣-carbon. A similar concept for the gas phase reactions of neutral glycolic acid has been postulated before based on theoretical studies on the mechanisms of the decomposition of ␣-hydroxycarboxylic and alkoxyacetic acids [11,12]. We believe that our experimental observations provide a support for ␣-lactone as an intermediate in dissociation reactions of negative ions of glycolic acid.…”
Section: Resultssupporting
confidence: 83%
“…According to product formations and the kinetic and thermodynamic parameters, the mechanisms of these eliminations may be considered as described in (7), (8), and (9):…”
Section: Ethyl Piperidine-3-carboxylatementioning
confidence: 99%
“…The acid intermediates of ethyl 1-methylpiperidine-3-carboxylate (reaction (8)) and ethyl piperidine-3-carboxylate (reaction (9)) are assumed to proceed through a six-membered cyclic transition state where the chair conformation appears to favor the elimination reaction. In the case of ethyl piperidine-3-carboxylate (reaction (9)), and the corresponding β-amino acid, i.e.…”
Section: Ethyl Piperidine-3-carboxylatementioning
confidence: 99%
See 1 more Smart Citation
“…In association with the aim of the present work, it is interesting to mention the valuable studies of the potential energy surface (PES) in the mechanistic considerations of the unimolecular the gas‐phase elimination kinetics of several 2‐substituted carboxylic acids 15–20. Calculations at the ab initio and Density Functional Theory (DFT) level of theory showed that the most reasonable mechanism is that which proceeds through the anchimeric assistance of the neighboring oxygen of CO of the carboxylic acid to the C α L bond polarization in the TS [reaction (3)].…”
Section: Introductionmentioning
confidence: 99%